Acinetobacter spp. as nosocomial pathogens: Epidemiology and resistance features - Almasaudi, Saad B. (Saudi J Biol Sci, 2018)
The genus Acinetobacter is a major cause of nosocomial infections; it is increasingly being associated with various epidemics and has become a widespread concern in a variety of hospitals worldwide. Multi-antibiotic resistant Acinetobacter baumannii, is now recognized to be of great clinical significance. Numerous reports relay to the spread of A. baumannii in the hospital settings which leads to enhanced nosocomial outbreaks associated with high death rates. However, many other Acinetobacter spp. also can cause nosocomial infections. This review focused on the role of Acinetobacter spp. as nosocomial pathogens in addition to their persistence, antimicrobial resistance patterns and epidemiology.